Memantine-Assisted Treatment of N-Methyl-D-Aspartate Receptor Antibody Encephalitis: A Mini Review - Liu FX; Qiu Q; Yan F; Feng YC; Wei HH; Li X (Neuropsychiatric Disease and Treatment)
Fei-Xiang Liu,1,2 Qi Qiu,1 Feng Yan,1 Yan-Chen Feng,2 Hong-Hui Wei,1,3 Xia Li1 1Shanghai Mental Health Center, Shanghai Jiaotong University, School of Medicine, Shanghai, People’s Republic of China; 2Department of Psychiatry and Psychology, The First Affiliated Hospital of Henan University of Chinese Medicine, Zhengzhou, People’s Republic of China; 3Zhejiang Provincial Mental Health Center, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Xia Li, Shanghai Mental Health Center, Shanghai Jiaotong University, School of Medicine, Shanghai, People’s Republic of China, Email ja_1023@hotmail.comAbstract: N-methyl-D-aspartate receptor encephalitis (NMDARE) presents serious neurological manifestations such as reduced consciousness, seizures, and movement disorders, which can escalate to coma or severe autonomic dysfunction. Treatment typically involves immunotherapy and tumor removal to mitigate the autoimmune response. Timely diagnosis and treatment are critical to prevent severe neurological impairment or death. Memantine, an NMDA receptor antagonist, has shown variable effectiveness in treating NMDARE according to several case reports, yet comprehensive analyses remain scarce. This mini review draws on five literature sources and eight case studies from databases including PubMed, Embase, the Cochrane Library, and Web of Science, highlighting both the potential and risks of memantine as an adjunct therapy. We explore how memantine may reduce symptoms by blocking excessive NMDA receptor (NMDAR) antibody binding, while potentially worsening symptoms by reducing extracellular NMDAR availability, thus impairing neuronal communication. This dual effect calls for further investigation into the optimal use and duration of memantine treatment in NMDARE management.Keywords: N-methyl-D-aspartate, N-methyl-D-aspartate receptor, N-methyl-D-aspartate receptor antibody, N-methyl-D-aspartate receptor antibody encephalitis, Memantine